PENGARUH GAYA KEPEMIMPINAN OTORITER DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT ARINA MULTI KARYA JAKARTA PUSAT - Zulia Putri Rosandra; Windy Gustia Wardani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The purpose of this research is to determine the influence of Authoritarian Leadership Style and Incentives on Employee Performance both partially and simultaneously at PT Arina Multi Karya in Central Jakarta. This research uses a descriptive associative method, with data collection conducted through a questionnaire survey. The sample used in this study is from saturated sampling, consisting of 68 respondents. Data analysis was performed using SPSS version 25. The analysis techniques used include instrument testing, validity testing, reliability testing, multicollinearity testing, heteroscedasticity testing, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. Based on the research results, the Authoritarian Leadership Style (X1) and Incentives (X2) yielded the multiple linear regression equation Y = 11.711 + 0.649 X1 + 0.697 X2. The hypothesis testing (t-test) for the Incentives variable (X2) shows that t hitung > t tabel (9.844 > 1.997) and a significance value of 0.000 < 0.050. Thus, Ho rejected and H2 accepted. This means that there is a partial positive and significant influence between Incentives (X2) on Performance (Y). The simultaneous hypothesis testing (F test) yielded a calculated F value > F table (61.836 > 3.14), which is also supported by a significant value of 0.000 < 0.050; thus, H3 is accepted, meaning there is a significant simultaneous influence between Authoritarian Leadership Style (X1) and Incentives (X2) on Employee Performance (Y). The coefficient of determination value has an influence of 64%, while the remaining 36% is influenced by other factors not included in the study.